The interaction of conductive surface of cylindrical sensor with electric field of uniformly charged rectilinear filament parallel to axis of cylinder - S. V. Biryukov; A. S. Kolmogorov; S. S. Kolmogorova (Омский научный вестник)
The article gives the calculation of the surface density of the electric charge induced on the conductive surface of the shell or the sensitive electrodes of the electrical induction electric field intensity sensor of cylindrical shape. The expressions found in the scientific literature for charge density are aimed at solving electrotechnical problems and require adaptation to the solution of problems in the calculation of electroinduction sensors. Therefore, the task of this article is to obtain suitable for calculation electroinduction sensors dependences of the charge density induced on the conductive cylindrical surface of the sensor body from the geometrical parameters of the electric field and the sensor. The mathematical investigations carried out made it possible to establish the dependence of the surface density of the electric charge for the case of conducting cylinder in the field of linear charge. These dependencies are analyzed and their reliability is confirmed. The result is a new form of representation of the surface electric charge density induced on the lateral surface of a conductive cylinder.